The Relationship Of Mothering Pattern With The Social Development Of Mentally Retarded Children - yuyun rahayu; Ima Sukmawati; Suhanda; D.Yunita Nafisah Faoziah (Science Midwifery, 2022)
Background: Mental retardation is a disorder characterized by limitations in intellectual aspects and adaptive behavior. Proper parenting of mentally retarded children will affect children's development, especially social development. The most important factor is the mother who is applied to the parenting pattern. Objective: To determine the relationship between maternal parenting and the social development of mentally retarded children. Method: The method is quantitative with a cross sectional approach. Data collection using a questionnaire, with 30 respondents. Results: from 30 respondents, the highest frequency was in the authoritarian category as many as 18 respondents (60.0%), while the development of children with mental retardation had the highest frequency in the less social development category as many as 19 people (63.3%). Conclusion: there is a significant relationship between maternal parenting and the social development of mentally retarded children with value (0.000). Keywords: Social development; Parenting; Mental Retardation